Heritage language learners of English: Linguistic gaps and cognitive strengths. - Balilah, Areej M. A.; Archibald, Lisa M. D.; Said, Fatma F. S. (International Journal of Speech-Language Pathology, 2023)
This study examined whether Heritage Language Learners (HLLs) of English display profile effects in their performance on knowledge- and processing-dependent measures relative to the standardised mean scores of monolingual speakers. The study also investigated the influence of several experiential factors on HLL performance. Participants were 59 Arabic-speaking HLLs from six to nine years old. The children completed a battery of linguistic tests in their L1 and L2, as well as cognitive measures of short-term and working memory and non-verbal intelligence. Significantly lower standardised scores were observed for HLLs as compared to the standardised mean scores on all Arabic/English language tasks except L2 word reading. HLLs scored at or above age-level expectations on cognitive measures except the Arabic nonword repetition task. Stepwise regression analyses examining variance in HLLs' performance, age and richness of environment consistently explained HLLs' performance in L1 Arabic, but different factors accounted for HLLs' performance in English depending on the task. Age was the only variable that consistently explained variance in performance on the cognitive measures. The results suggest that processing-dependent measures may be less sensitive to difference in language experience than traditional knowledge-based measures such as standardised measures of language and vocabulary.